Anthropometric Study of the Heel Breadth among 5 to 10 Years Old Bangladeshi Children - Ismatsara, Mst; Epsi, Effat Zerin; Haque, Shah Md Atiqul (Community Based Medical Journal, 2026)
A cross-sectional, descriptive study was conducted in the Department of Anatomy, Mymensingh Medical College, Mymensingh, Bangladesh, to determine heel breadth among 5 to 10 years old children as well as to explore sexual dimorphism, if any. A nonrandom purposive sampling technique was adopted for sample collection. Any kind of foot deformity due to either from inherited or physical injury were excluded to construct standard measurement. A total of 109 Bangladeshi children (70 male and 39 female) hailing from different areas of Fulbaria, Trishal, Haluaghat, Phulpur and Muktagacha Upazila under Mymensingh district, aged between 5 and 10 years, were finally included in this study. Heel breadth was measured using Vernier slide calipers. Children were requested to stand with weight distributed equally on both feet. The legs were perpendicular to the feet. The mean heel breadth of right side of 5, 6, 7, 8, 9 and 10 years aged male children were 3.92±.49 cm, 4.21±.44 cm, 3.87±.54 cm, 4.41±.39 cm, 4.61±.56 cm and 4.34±.61 cm respectively, while 3.86±.43 cm, 3.50±.24 cm, 4.11±.59 cm, 3.94±.56 cm, 3.27±.33 cm and 3.91±.54 cm among female children respectively. The mean heel breadth of left side of 5, 6, 7, 8, 9 and 10 years aged male children were 3.92±.49 cm, 4.18±.44 cm, 3.84±.52 cm, 4.36±.39 cm, 4.54±.53 cm and 4.30±.60 cm respectively and 3.81±.41 cm, 3.50 ±.24 cm, 4.07±.59 cm, 3.88±.60 cm, 3.27±.33 cm and 3.86±.51 cm among females respectively. Comparison of heel breadth showed no significant difference between male and female (p>0.05), except in 6 and 9 years old children, the difference was statistically significant (p<0.05). The present anthropometric study was designed to construct data of 5 to 10 years aged Bangladeshi children regarding heel breadth and an attempt has been made out to create interest among the researchers for future study. Our study findings are expected to enrich the information pool for use in research and practice in multiple disciplines, e.g., anatomy, orthopaedics, forensic medicine, plastic surgery, radiology, podiatry, archeology, anthropology and nutrition science. CBMJ 2026 January: vol. 15 no. 01 P: 22-25